Overview of The Destruction of Inactive Medical Record Files at The Kencana Serang Level IV Hospital in 2023 - Heru Indra Cahya; Sri Susanti (Journal Of Applied Health Research And Development, 2023)
Kencana Serang Level IV Hospital has destroyed inactive outpatient and inpatient medical record files. Kencana Serang Level IV Hospital in carrying out the transfer of inactive medical records is still united with the medical record room which is still active but the storage shelves are different. And the Medical Record section of the filing room already has tools for destroying Medical Record files but they have not been used for destruction which has resulted in piles of medical record files. The purpose of this study was to determine the implementation of the destruction of inactive medical record files at Kencana Serang Level IV Hospital in 2023. The type of research used was descriptive qualitative research. The population of this study were all officers who worked in the medical record unit at Kencana Hospital Level IV Kencana Serang and the sample of this study were the head of the Medical Record Installation and Filing Officer for Hospital Level IV Kencana Serang. At Kencana Serang Level IV Hospital, the facilities and infrastructure used for extermination are computers, scanners, scissors and cardboard. For paper destruction tools already available but not yet used, Medical Records at Kencana Hospital in Serang City which are destroyed in the category of Medical Records that have no use value or are more than 5 years old, and obstacles to destruction are Lack of Human Resources (HR) and place or room.